2021
DOI: 10.1007/s00181-021-02087-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of economic uncertainty caused by COVID-19 on renewable energy stocks

Abstract: By employing time–frequency-domain frameworks, this study analyzes the spillover effects of news-based economic uncertainty caused by the pandemic on three renewable energy stock indices in the USA, Europe, and the world. The empirical results reveal that the total spillover from economic uncertainty to the three renewable energy stock returns was concentrated at a high frequency, whereas those to volatilities appeared at low frequencies. Utilizing a rolling-window method, we observed that the impact of uncert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…The novel coronavirus has had an unprecedently effect on the alternative energy sector. Liu et al [43] found that the COVID-19 pandemic had a more significant impact on the alternative energy sector than the global financial crisis did in terms of stock price returns and volatilities. Studies on the impact of COVID-19 on the alternative energy sector indicate the adverse effects of the pandemic during its initial phase.…”
Section: Introductionmentioning
confidence: 99%
“…The novel coronavirus has had an unprecedently effect on the alternative energy sector. Liu et al [43] found that the COVID-19 pandemic had a more significant impact on the alternative energy sector than the global financial crisis did in terms of stock price returns and volatilities. Studies on the impact of COVID-19 on the alternative energy sector indicate the adverse effects of the pandemic during its initial phase.…”
Section: Introductionmentioning
confidence: 99%
“…There was a negative effect on the quality of the population's mental well-being, an increase in the levels of anxiety, depression and alcohol abuse 5 , and an increase in cases of depression [5][6][7][8] , anxiety [5][6][7][8] , stress [6][7][8] , panic disorder 3 , insomnia 8 , fear 4,7,8 and anger 5 in different populations. The financial losses in this pandemic episode were an additional factor to the psychosocial risk 9,10 ; in particular, suicide rates increased in proportion to a rise in unemployment in Canada 11 , a relationship already described in Brazil in the pre-pandemic period 12 .…”
Section: Introductionmentioning
confidence: 69%
“…We hypothesized a positive association between GDP and stock market index to determine whether stock market index can be a predictor of economic activity using quarterly data. We assume that stock market indices can reflect future expected economic outcomes, as they are made up of an aggregated measure of investment performance and can serve as a sentiment indicator that may reflect on the expected economy [1,[13][14][15].…”
Section: Hypothesis 1 (H1): Gdp and Stock Market Indexmentioning
confidence: 99%